Ducto arterioso patente em cães: indução experimental por toracotomia, correção por cirurgia torácica vídeo-assistida (CTVA) e avaliação de aderências por toracoscopia - Richter, Rosana Keller (2006)
Aiming at to develop a model of experimental induction of patent ductus arterious by thoracotomy, to study a corrective technique for the experimental defect by video-assisted thoracic surgery (VATS) and to evaluate eventual adhesions by thoracoscopy, three experiments were done. For each experiment were used 14 adult mongrel dogs, weighting 10 to 20 kg. In the PDA induction experiment it was possible to implant the autologous graft in the same anatomical localization of the congenital PDA, the left subclavy artery can be used as a patent graft simulating PDA, and this model did not cause cardiac injuries (detectable by visualization and CK and CKMB dosages). In conclusion, this model can be used as a base for new researches for the treatment of PDA, for the training of surgical correction technics and for other studies in veterinary medicine cardiology. In the proposed correction technique, three work ports and the optics were enough and adequately located for the correction of the PDA; surgical materials for vascular surgery can be used for the accomplishment of this technique; the positioning of the surgical team, the patient, the equipments and the instruments were adequated; the knot of Roeder was effective; this correction technique was viable up to five days after the induction of the PDA. In conclusion, this technique is effective and can be used on clinical cases for the occlusion of the congenital PDA and in the training of video-endoscopic surgeons. In the adhesions evaluation study, it was observed that thoracotomy and VATS induced the adhesions formation; these adhesions were located along VATS and thoracotomy incisions, and their extension was smaller after VATS, due to smaller tissue damage extension; it was possible to lise the adhesions by thoracoscopy in up to five days of postoperative, being necessary two work ports; the increase of the CK seric levels was proportional to the tissue damage. In conclusion, thoracotomy and VATS induce the formation of adhesions. High incidence of adhesions post thoracotomy and post VATS may lead to serious surgical risks and requires special care in future surgical reinterventions. This scintific work was approved by the animal welfare committee (012/2005) of the Universidade Federal de Santa Maria and all the animals used in this work were adopted.